Analysis of Taxpayer Compliance in Paying Taxes Swallow's Nest at the Regional Revenue Agency In Majene Regency - Mukhram, Muhammad; Hajar, St. (Jurnal Ekonomi, 2024)
Majene Regency has regulations related to the swallow's nest tax, which is regulated in Regent Regulation (PERBUP) Number 33 of 2015 and Regional Regulation (PERDA) Number 8 of 2015. This regulation governs the procedures for implementing swallow's nest tax management as one of the potential regional revenues. However, in the field, taxpayer compliance is still low. Many swallow's nest entrepreneurs are not honest in providing information regarding the number of production and the time of reporting. Some taxpayers also do not understand or even ignore the existing rules. This study evaluates the compliance of swallow's nest taxpayers, including registration as a taxpayer, filling and depositing the Regional Tax Notification Letter (SPTPD), tax calculation and payment, and arrears payment to the regional treasury. The study results show that the four compliance indicators have not run optimally. The Regional Revenue Agency (BAPENDA) of Majene Regency needs to increase supervision and take decisive steps, including applying administrative sanctions to confiscate assets against non-compliant taxpayers. This effort is expected to improve taxpayer compliance and optimize wallet bird's nest tax revenue.